2022
DOI: 10.3390/foods11182924
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Multidrug-Resistant Salmonella enterica Serovars in Buffalo Meat in Egypt

Abstract: The current study aimed to investigate the presence of Salmonella spp. prevalence in buffalo meat in Egypt, along with studying the antimicrobial susceptibility of the recovered isolates. Salmonella spp. was detected in 25% of tested buffalo meat. A total of 53 (100%) isolates were genetically verified by PCR as Salmonella, based on the detection of the invA gene. The stn and hilA genes were detected in 71.7% (38/53), and 83.0% (44/53) of the recovered isolates, respectively. Salmonella Enteritidis (11/53; 20.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The results of antibiotic susceptibility testing are illustrated in (Table 2 ); the recovered NTS isolates showed 100% resistance to clindamycin, followed by streptomycin (98.85). These results are consistent with those obtained by many previous studies [ 15 , 24 ] and It was observed that 100% of isolates from both animals and humans were resistant to clindamycin, although its use in large animals was limited. This demonstrated the cross-transmission of NTS between humans and animals (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of antibiotic susceptibility testing are illustrated in (Table 2 ); the recovered NTS isolates showed 100% resistance to clindamycin, followed by streptomycin (98.85). These results are consistent with those obtained by many previous studies [ 15 , 24 ] and It was observed that 100% of isolates from both animals and humans were resistant to clindamycin, although its use in large animals was limited. This demonstrated the cross-transmission of NTS between humans and animals (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Data in (Table 4 ) illustrated that stn gene was found in 72.22% of the tested isolates. Similarly, the stn genes were detected in 71.7% of the tested isolates in Egypt [ 24 ]. On the other hand, the stn gene could be detected in all Salmonella isolates [ 34 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, all the tested bacteria were identified as MDR because they resisted at least one antibiotic within more than three different classes. MDR Salmonella have been isolated previously from Egypt ( Abdelhakim et al, 2011 ; Abdel-Maksoud et al, 2015 ; Mahmoud et al, 2018 ; Merwad and Abdel-Haliem, 2018 ; Esmael et al, 2021b ; Abd-Elghany et al, 2022 ). In Egypt there are no boundaries on antibiotic remedies and antibiotics can be acquired easily without any medical prescription from drugstores and pharmacies ( Sobhy et al, 2012 ; Sabry et al, 2014 ; Awad et al, 2016 ; Esmael et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…carry invA , which allow bacteria to invade epithelium cells of the human gastrointestinal tract [ 17 ]. Therefore, the invA gene has been widely used as a genetic marker to confirm the presence of Salmonella isolates [ 18 ].…”
Section: Introductionmentioning
confidence: 99%